Sleep Disorder and its Treatment: From Nature to Laboratory - Varshney, Mohit; Saha, Supriyo; Prinsa, Prinsa; Jakhmola, Vikash (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
Sleep is the natural cellular repair mechanism to improve and restore central neural mechanism, memory, hormonal imbalance, and finally, cell rejuvenation. Sleep disorder is characterized by insomnia, circadian rhythm disorder (CRD), sleep apnea, narcolepsy, parasomnia, and restless leg syndrome (RLS) or periodic limb movement disorder (PLMD). Both oversleeping and less sleeping are associated with sleep disorders (SD). Anxiety, schizophrenia, weight loss/gain, hypothyroidism, and oxidative stress are the most common outcomes of SD. There is also a genetic explanation behind circadian rhythmicity, circadian disorder, narcolepsy-cataplexy syndrome, fatal familial insomnia, and somnambulism. Excessive work pressure, stress, and consumption of caffeine and alcohol collectively push a person toward sleep deprivation. Anxiety, schizophrenia, weight loss/gain, hypothyroidism, and oxidative stress are the most common outcomes of SD. Adenosine, melatonin, dopamine, serotonin, gamma amino butyric acid (GABA), orexin, and histamine regulate SDs by various pathways. Among natural sources, Centella asiatica, Bacopa monnieri, Acorus calamus, Withania somnifera, Nardostachys jatamansi, Poria cocos is, Valeriana officinalis, Matricaria chamomilla, Lavandula angustifolia, Nelumbo nucifera, Melissa officinalis, Convolvulus pluricaulis, Camellia sinensis, Ziziphus jujube, Datura stramonium, Zhizhipus jujube, Passiflora incarnata, and Moringa oleifera showed remarkable effects on different forms of SDs through GABAA, serotonin, and melatonin receptors. Pramipexole, ropinirole, rotigotine, clonazepam, lorazepam, estazolam, zolpidem, lemborexant, daridorexant, and suvorexant showed its activity in the treatment of SDs as a dopamine agonist, inhibitor of GABAA receptor, dual orexin receptor antagonist, respectively. This article focused on the types of SDs, the effects of SDs on mental health, receptors involved in the sleep cycle, and the impact of natural molecules and synthetic molecules in the management of SDs.